Answer:
Explanation:
Given the expression (((x^3)^2))^2
a) Differentiating the function with respect to x using chain rule.
Given y = (((x^3)^2))^2
Let u = (x³)²
y = u²; dy/du = 2u
Let p = x³; dp/dx = 3x²
u = p²; du/dp = 2p
Applying the chain rule formula:
dy/dx = dy/du • du/dp • dp/dx
substitute in the formula
dy/dx = 2u•2p•3x²
Since u = (x³)² and p = x³
dy/dx = 2(x³)²(2x³)(3x²)
dy/dx = 12x^6•x^5
dy/dx = 12x¹¹
b) Using property of exponent
y = (((x^3)^2))^2
y = (x^6)²
y = x¹²
dy/dx = 12x^12-1
dy/dx = 12x^11